Public health in 1948 : Remarkable statistics. The first months of the National Health Service
1950-03-31 1950 1950s 8 pages MINISTRY OF HEALTH Public Health in 1948: Remarkable Statistics The first months of the National Health Service. New low records in health statistics were set up in 1948 - a year also made notable by the inauguration of the National Health Service. The Ministry of Health's Annual Report* for the year ended 31st March, 1949 which is published today (Friday, 31st March), records: 1. The National Health Service was inaugurated on 5th July, 1948; of its early months the Minister ( Mr. Aneurin Bevan ) says, "Since its inception the Health Service has been subjected to sustained scrutiny both at home and abroad - indeed, it has excited worldwide attention - and the demands made upon it during the first nine months of its existence have in some directions severely taxed its strength and capacity. This has been a testing time, but it has proved that the structure of the Service is generally sound and that the foundations have been securely laid." 2. The Chief Medical Officer (Sir Wilson Jameson) describes the vital statistics as "wonderful". A total death rate of 10.8 with a civilian death rate of 11.0, both the lowest on record, gave a smaller number of deaths than any year since 1930, when there were 3,000,000 fewer people in the country. Compared with 1938 (which had the lowest standardized mortality of any year before the second world war) the mortality index at all ages showed a 20 per cent decline. There were striking reductions in deaths from a number of diseases. 3. In the words of the Minister, "the last vestiges of a Poor Law system that had persisted since Elizabethan days were finally removed from the Statute Book by the National Assistance Act". 4. The number of permanent houses finished during the year to 31st March, 1949, (more than 200,000) was the highest since the war. 5. In the field of local government, the system of "block grants", which had operated since 1929, was brought to an end by the Local Government Act, 1948, which introduced "equalisation grants" in their place. PART I CENTENARY OF THE PUBLIC HEALTH SERVICE The year 1948, by its remarkable vital statistics and by the coming into force of the National Health Service, fittingly commemorated the celebrations marking the first hundred years of the Public Health Service. The first Public Health Act was passed in 1848. The year enjoyed the sequence of a fine warm winter, a lively spring, a cool wet August and an exceptionally mild autumn. These climatic factors, and the absence of influenza, combined to make the vital statistics of the year memorable. A total death rate of 10.8 per 1,000 and a civilian death rate of 11.0, both the lowest on record, gave a smaller number of deaths than in any year since 1930, when there were 3,000,000 fewer people in the country. P.2 - 1 - * Report of the Ministry of Health for the year ended 31st March, 1949, including the Report of the Chief Medical Officer on the state of the Public Health for the year ended 31st December, 1948. Cmd. No.7910 H.M. Stationery Office (price 7/6 net. post free 7/11). 292/847/5/38